Impact of cell temperature on the performance of a rooftop photovoltaic system of 2.56 kWp at Universitas Pamulang - Ojak Abdul Rozak; Mohd Zamri Ibrahim; Muhamad Zalani Daud; Syaiful Bakhri; Rifqi Muwaffiq (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The performance of solar panels greatly determines the electrical energy production of a solar power generation system. The decrease in performance has an impact on efficiency, output power, output voltage and current. Currently, at Universitas Pamulang a solar photovoltaic system (PV) is installed with a capacity of 2.56 kWp since 2018. However, no performance test and analysis have been conducted to determine its level of efficiency and reliability. This paper presents an experimental method used for performance testing of a 320 W mono-crystalline solar panel, measuring from 08.00 AM to 4.00 PM, using the solar survey 200R to measure solar irradiation, ambient and cell temperature. A digital multimeter CD800a was used to measure Voc and a PV200 tester used to measure voltage and current output. The results revealed that at an ambient temperature of 38°C and cell temperature 50.9°C, the intensity of solar radiation was 702.7 W/m2 and output voltage of 42.9 V with a performance of 78.37% and an efficiency of 27.73% was due to an increase cell temperature. Low-efficiency values with high cell temperatures indicate that this system requires an external solar panel cooling system.